2020
DOI: 10.1177/1479973120964814
|View full text |Cite
|
Sign up to set email alerts
|

The quality of COPD care in German general practice—A cross-sectional study

Abstract: Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a common health problem to be dealt with in primary care. Little is known about the quality of care provided for patients with COPD in Germany. Therefore, we wanted to assess the current quality of care delivered by a primary care network (PCN) for patients with COPD. Methods: A cross-sectional study was conducted in collaboration with a primary care network (PCN). All patients of the PCN aged 40 years and older with a diagnosis of COPD were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Burkhardt and Pankow reported that 80% of primary care physicians’ offices in Germany were equipped with spirometers [ 6 ]. At the same time, Heinmüller et al reported that, for Germany in 2020, of 2568 patients with COPD, 29% had had a spirometry test within the previous year [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Burkhardt and Pankow reported that 80% of primary care physicians’ offices in Germany were equipped with spirometers [ 6 ]. At the same time, Heinmüller et al reported that, for Germany in 2020, of 2568 patients with COPD, 29% had had a spirometry test within the previous year [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While this paper highlights multiple barriers in referring patients with COPD to PR, barriers to high-quality healthcare for patients with COPD span throughout the disease trajectory and persist across health service provisions worldwide 40–42. It is interesting to note that few participants in our study thought that a financial incentive was important.…”
Section: Discussionmentioning
confidence: 87%
“…While this paper highlights multiple barriers in referring patients with COPD to PR, barriers to high-quality healthcare for patients with COPD span throughout the disease Open access trajectory and persist across health service provisions worldwide. [40][41][42] It is interesting to note that few participants in our study thought that a financial incentive was important. It is however difficult to assess this given that face-to-face PR programmes were suspended across the country as a result of the COVID-19 pandemic.…”
Section: Implications For Policy and Practicementioning
confidence: 87%
“…It is possible that documentation of smoking is most often missed when the patient does not smoke, since then no intervention is needed. Prior studies have reported that 44–95% of patients with asthma, COPD or diabetes have a smoking status documented in primary care EHR [ 21–24 ]. Studies in secondary health care are scarce.…”
Section: Discussionmentioning
confidence: 99%